Rancang Bangun Alat Penanam Benih Kacang Tanah - Safridatul Audah; Rusda Eka Rahma; Asmara Bakti; Ria Darma (Jurnal Inotera, 2017)
Peanuts or Latin Arachis hypoghea is one of the crops of palawija that has long been known to our farmers as a production plant. One of the causes that inhibits peanut productivity is because the planting process is still done manually using human power. To overcome this, the system was designed to design a tool for planting peanuts mechanically. The design of this equipment begins with the size and shape of the instrument itself with the aim of producing a peanut plant that works in human thrust strength, this study brings significance to farmers to save costs to pay workers, otherwise farmers work efficiently and effectively.